2019
DOI: 10.1021/acs.analchem.9b03172
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Sensor Array Based on Wulff-Type Boronate Functionalized AgNPs at Various pH for Bacteria Identification

Abstract: The efficient identification of bacteria is of considerable significance in clinical diagnosis. Herein, a novel colorimetric sensor array was developed for the detection and identification of bacteria based on the specific affinity and electrostatic interaction between Wulff-type 4-mercaptophenylboronic acid (MPBA)-mercaptoethylamine (MA) cofunctionalized AgNPs (MPBA-MA@AgNPs) and bacteria at various pH. In the neutral and alkaline conditions, AgNPs tended to be dispersed due to the specific affinity between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…As a conventional achiral chemical‐capturing molecule, MPBA undergoes pH‐dependent structural changes, which produces different SERS spectral patterns of MPBA under different pH conditions (Supporting Information, Figure S13 A). It is necessary to investigate the SERS spectra of the mixed‐thiol SAMs on the Au NRs arrays in solution at pH levels ranging from 1 to 13 to elucidate at which pH the chiral discrimination sensing system displays optimal discrimination performance.…”
Section: Resultsmentioning
confidence: 99%
“…As a conventional achiral chemical‐capturing molecule, MPBA undergoes pH‐dependent structural changes, which produces different SERS spectral patterns of MPBA under different pH conditions (Supporting Information, Figure S13 A). It is necessary to investigate the SERS spectra of the mixed‐thiol SAMs on the Au NRs arrays in solution at pH levels ranging from 1 to 13 to elucidate at which pH the chiral discrimination sensing system displays optimal discrimination performance.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, with the development of sensor arrays, it has become possible to detect and determine bacteria simultaneously [ 296 , 297 , 298 , 299 , 300 ]. The detection mechanism is based on changes in the optical or electrical properties of the indicator after the interaction with bacteria or metabolites emitted from the bacterial growth.…”
Section: Application Of Paper Biosensors In the Detection Of Toxic Materialsmentioning
confidence: 99%
“…The covalent complexes form at a high pH value (basic) and are dissociated at a low pH value (acidic). [28,29] Wu et al [30] reported a sensor array for bacterial detection at various pH values using MPBA-mercaptoethylamine (MA)-cofunctionalized AgNPs (Figure 1B). In this research, Wulff-type boronate that has amines adjacent to boronic acid was selected as the recognition molecule.…”
Section: Boronic Acid With Cis-diol Group Of Saccharidementioning
confidence: 99%